Th2 Regulation of Viral Myocarditis in Mice: Different Roles for TLR3 versus TRIF in Progression to Chronic Disease - Eric D. Abston; Michael J. Coronado; Adriana Bucek; Djahida Bedja; Jaewook Shin; Joseph B. Kim; Eunyong Kim; Kathleen L. Gabrielson; Dimitrios Georgakopoulos; Wayne Mitzner; DeLisa Fairweather (Clinical and Developmental Immunology)
Viral infections are able to induce autoimmune inflammation in the heart. Here, we investigated the role of virus-activated Toll-like receptor (TLR)3 and its adaptor TRIF on the development of autoimmune coxsackievirus B3 (CVB3) myocarditis in mice. Although TLR3- or TRIF-deficient mice developed similarly worse acute CVB3 myocarditis and viral replication compared to control mice, disease was significantly worse in TRIF compared to TLR3-deficient mice. Interestingly, TLR3-deficient mice developed an interleukin (IL)-4-dominant T helper (Th)2 response during acute CVB3 myocarditis with elevated markers of alternative activation, while TRIF-deficient mice elevated the Th2-associated cytokine IL-33. Treatment of TLR3-deficient mice with recombinant IL-33 improved heart function indicating that elevated IL-33 in the context of a classic Th2-driven response protects against autoimmune heart disease. We show for the first time that TLR3 versus TRIF deficiency results in different Th2 responses that uniquely influence the progression to chronic myocarditis.